A case report of serous carcinoma of the uterine corpus - Ana Kocevska; Emil Bajalski; Bashkim Ismaili; Dimitar Georgiev; Kristina Skeparovska; Shenol Tahir; Aleksandar Nakov (My University, 2022)
In the Republic of North Macedonia, in 2020, there were 369 new cases of cancer of the uterine body, which were 10.9% of all new cases of malignancies and was the third most common in women, after breast cancer and colorectal cancer. Endometrial polyps are common pathological findings and their prevalence is between 16% to 34%. The prevalence of malignant and premalignant lesions found in the endometrial polyps ranges from 0.8% to 4.8%. Uterine serous carcinoma is an aggressive variant of EC that accounts for only 5-10% of all EC, but is related with 80% of endometrial cancer–related deaths. It is not related with increased estrogen levels and atypical endometrial hyperplasia. They arise in a background of atrophic endometrium or endometrial polyps in postmenopausal women. We present a case of 72 years old patient with serous carcinoma of the uterine corpus that arises on endometrial polyp. She was 20 years postmenopausal and bleeding was present. The transvaginal ultrasound examination showed that heterogeneous and irregular endometrial thickening was present. We performed fractionated explorative curettage. The histopathological report showed the presence of the parts of an endometrial polyp with surface that is coated with atrophic endometrium, and in parts it was coated with malignantly altered endometrium. The morphology of serous endometrial carcinoma with complex papillary and glandular architecture was present. Pathological mitoses have been verified. Lymphovascular invasion or infiltration of the cervical stroma were not found. Total abdominal hysterectomy with bilateral salpingo-oophorectomy was performed. Histopathological analysis of the operative material showed the absence of lymphovascular infiltration but present infiltration of the cervical stroma (pTNM= pT2 pNx pMx R0 L0 V0 Stage II). The patient was referred for further treatment to an oncologist.
Abstracts of the 32nd World Congress on Ultrasound in Obstetrics and Gynecology, 16–18 September 2022, London, UK & Virtual